Pretreatment on anaerobic sludge for enhancement of biohydrogen production from cassava processing wastewater - Lamaison, Franciele do Carmo; Fragata, Rafael; Antônio, Regina Vasconcellos; Amante, Edna Regina; Reginatto, Valeria (Acta Scientiarum. Technology, 2014)
Methods for the enrichment of an anaerobic sludge with H2-producing bacteria have been compared by using cassava processing wastewater as substrate. The sludge was submitted to three different pretreatments: 1) heat pretreatment by boiling at 98Â°C for 15 min., 2) heat pretreatment followed by sludge washout in a Continuous Stirring Tank Reactor (CSTR) operated at a dilution rate (D) of 0.021 h-1, and 3) sludge washout as the sole enrichment method. The pretreated sludge and the sludge without pretreatment (control) were employed in the seeding of 4 batch bioreactors, in order to verify the volume and composition of the generated biogas. Maximum H2 production rates (Rm) from the pretreated sludges were estimated by the modified Gompertz model. Compared to the control, H2 production was ca. 4 times higher for the sludge submitted to the heat pretreatment only and for the sludge subjected to heat pretreatment combined with washout, and 10 times higher for washout. These findings demonstrated that the use of sludge washout as the sole sludge pretreatment method was the most effective in terms of H2 production, as compared to the heat and to the combined heat and washout pretreatments.